Modification of adsorbents for high CO2 content capture from stranded natural gas reserve: A critical review - Mohd Noor, N.I. (Trans Tech Publications Ltd, 2014)
Carbon dioxide (CO2) commonly exists as undesirable component in natural gas streams. The continuous growing of the global demand makes it necessary to overcome the high CO2 content obstacle of stranded reserves. A wide variety of acid gas removal technologies have been developed, including chemical and physical absorption processes but none of them can combine he high efficiency and economic energy consumption. Each process has its own advantages and disadvantages. Using of adsorbents increasingly being selected for newer projects, especially for applications that have large flow, high CO2 content and located in remote locations such as offshore where compact and highly effective technology is required. This review highlights the importance of adsorbent modification on CO2 removal from natural gas reserve at high pressure and temperature using physical adsorbents such as zeolite and molecular sieve. Then, the focus is turned on the adsorbents chemical modification using organic amines to improve the adsorption efficiency towards CO2. Â© (2014) Trans Tech Publications, Switzerland.